Structure of a Scarabaeinae community: a numerical-behavioural study (Coleoptera: Scarabaeinae) - Kohlmann, Bert; Sánchez Colón, Salvador (Instituto de Ecología, A.C., 1984)
The structure of a Scarabaeinae community in the tropical mountains of México is studied using trophic and reproductiva characters, which were analyzed by multivariate methods (cluster and ordination analysis). The results suggest that spatial-temporal characters play an important role ¡n structuring the community. These characters along with resource utilization behaviour suggest that competition has a community ordering process. Species richness in this area ¡s high due to a biogeographíc overlap. The obtained results show the great potential of using multivariate analysis techniques for this type of study.